Papillary Thyroid Cancer: Prevalence, Diagnosis Methods, Symptoms and Management Options in Tripoli, Libya - Alshintari, Mohamed; Esraa Dhaw,; Mayar Alagnaf, (AlQalam Journal of Medical and Applied Sciences, 2025)
Papillary thyroid cancer is the most common type of thyroid cancer, affecting the thyroid gland in the neck. It can cause the thyroid gland to swell and lead to symptoms such as difficulty swallowing and shortness of breath. Treatment for papillary thyroid cancer usually involves surgically removing the affected gland and undergoing radiation or chemotherapy if necessary. It is important to detect this type of cancer in its early stages to increase the chances of recovery. Papillary thyroid cancer is a public health concern due to its recent increase in prevalence in the world. This study aimed to evaluate the prevalence of papillary thyroid cancer among the population in the Tripoli area, Libya, and to evaluate some of the contributing factors, including gender, age, and iodine deficiency in the body. A study was conducted on 200 people, women and men, covering most age groups from two hospitals (Tripoli University Hospital & Al-Zawiya Street Central Hospital) in the Tripoli region, western Libya. The extent of the disease was determined using a questionnaire filled out form patient files. In general, the prevalence of papillary thyroid cancer was (27.5%). Of which (75.9%) are females and (24.1%) are males. In addition, the highest prevalence rate was in the age group of 36-55 years. The most common cause of infection is a lack of Iodine in the body, and the most prominent symptom that explains the disease is the emergence of lymph nodes in the neck. سرطان الغدة الدرقية الحليمي هو النوع الأكثر شيوعا من سرطان الغدة الدرقية، ويؤثر على الغدة الدرقية في الرقبة. ويمكن أن يسبب تضخم الغدة الدرقية ويؤدي إلى أعراض مثل صعوبة البلع وضيق التنفس. وعادة ما يتضمن علاج سرطان الغدة الدرقية الحليمي إزالة الغدة المصابة جراحياً والخضوع للعلاج الإشعاعي أو الكيميائي إذا لزم الأمر. ومن المهم اكتشاف هذا النوع من السرطان في مراحله المبكرة لزيادة فرص الشفاء. ويعتبر سرطان الغدة الدرقية الحليمي مصدر قلق للصحة العامة بسبب الزيادة الأخيرة في انتشاره في العالم. وهدفت هذه الدراسة إلى تقييم انتشار سرطان الغدة الدرقية الحليمي بين السكان في منطقة طرابلس، ليبيا، وتقييم بعض العوامل المساهمة، بما في ذلك الجنس والعمر ونقص اليود في الجسم. أجريت الدراسة على 200 شخص، من النساء والرجال، غطت معظم الفئات العمرية من مستشفيين (مستشفى طرابلس الجامعي ومستشفى شارع الزاوية المركزي) في منطقة طرابلس، غرب ليبيا. وتم تحديد مدى انتشار المرض باستخدام استبيان تم تعبئته في ملفات المرضى. وبشكل عام بلغ معدل انتشار سرطان الغدة الدرقية الحليمي (27.5%)، منها (75.9%) إناث و(24.1%) ذكور، كما أن أعلى معدل انتشار كان في الفئة العمرية (36-55) سنة، والسبب الأكثر شيوعاً للإصابة هو نقص اليود في الجسم، وأبرز الأعراض التي تفسر المرض هو ظهور الغدد الليمفاوية في الرقبة